Inhibition of mitochondrial respiration has fundamentally different effects on proliferation, cell survival and stress response in immature versus differentiated cardiomyocyte cell lines - Grün, Bent; Tirre, Michaela; Pyschny, Simon; Singh, Vijay; Kehl, Hans-Gerd; Jux, Christian; Drenckhahn, Jörg-Detlef (Frontiers in Cell and Developmental Biology, 2022)
Myocardial tissue homeostasis is critically important for heart development, growth and function throughout the life course. The loss of cardiomyocytes under pathological conditions ultimately leads to cardiovascular disease due to the limited regenerative capacity of the postnatal mammalian heart. Inhibition of electron transport along the mitochondrial respiratory chain causes cellular stress characterized by ATP depletion as well as excessive generation of reactive oxygen species. Adult cardiomyocytes are highly susceptible to mitochondrial dysfunction whereas embryonic cardiomyocytes in the mouse heart have been shown to be resistant towards mitochondrial complex III inhibition. To functionally characterize the molecular mechanisms mediating this stress tolerance, we used H9c2 cells as an in vitro model for immature cardiomyoblasts and treated them with various inhibitors of mitochondrial respiration. The complex I inhibitor rotenone rapidly induced cell cycle arrest and apoptosis whereas the complex III inhibitor antimycin A (AMA) had no effect on proliferation and only mildly increased cell death. HL-1 cells, a differentiated and contractile cardiomyocyte cell line from mouse atrium, were highly susceptible to AMA treatment evident by cell cycle arrest and death. AMA induced various stress response mechanisms in H9c2 cells, such as the mitochondrial unfolded protein response (UPRmt), integrated stress response (ISR), heat shock response (HSR) and antioxidative defense. Inhibition of the UPR, ISR and HSR by siRNA mediated knock down of key components does not impair growth of H9c2 cells upon AMA treatment. In contrast, knock down of NRF2, an important transcriptional regulator of genes involved in detoxification of reactive oxygen species, reduces growth of H9c2 cells upon AMA treatment. Various approaches to activate cell protective mechanisms and alleviate oxidative stress in HL-1 cells failed to rescue them from AMA induced growth arrest and death. In summary, these data show that the site of electron transport interruption along the mitochondrial respiratory chain determines cell fate in immature cardiomyoblasts. The study furthermore points to fundamental differences in stress tolerance and cell survival between immature and differentiated cardiomyocytes which may underlie the growth plasticity of embryonic cardiomyocytes during heart development but also highlight the obstacles of cardioprotective therapies in the adult heart.